Ethics, mental health, and COVID-19 - Perales, Alberto (2020)
COVID-19, whose first case was confirmed in Peru in March 2020, revealed many deficiencies in our country, not only in its health systems, but also with respect to democracy and moral values of Peruvian society. This paper reviews both ethical and mental health problems, pointing out difficulties between the state and the civil society for working together against the pandemics, and also stating the presence of population groups that instead of protecting themselves, ignore regulations for social distancing and isolation facilitating the transmission of the viral agent. An explanatory scientific and moral hypothesis is proposed aiming to explain such conduct. Also, taking advantage of all the energy generated by a crisis and the possibility of turning this into a developmental current, some measures to be taken by the government are proposed, with the purpose of trying to correct mental health problems that have been affecting the Peruvian society for a long time, aiming to improve its moral and economic development.